The prevalenceof risk factors for decreasing adhesionin he Therapywith Enfuvirtidain HIV infected users in treatmentin centers of referencein Porto alegre /RS - Santos, Thiago C (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: In 2005 the Ministry Health of Brazil provided Enfuvirtide, the first inhibitor of fusion, a new class of anti-retroviraes with extracellular action.The difficulties described by the first users, in one of the reference centers, and the lack of studies with the users of the Public Health Department, hadmotivated this research. Objective: to identify risk factors for low adhesion to the treatment with enfuvirtida. Methods: 37 people from Porto Alegre had beeninterviewed, the total population of users of enfuvirtide in this city until October, 2006. Results: had presented that 27% of the patients had already thoughtabout giving up the treatment, 22,2% had forgotten to take the dose in the last 30 days and 45,9% do not know the difference between HIV and AIDS. The localadverse effect had occurred in all the users, pain in the application places were present in 81,1% of the cases, but it did not interfere in daily activities (70,3%).Concerning applications, 28,9% had not had a first supervised dose, 27% did not make a massage after the applications, 46% of the patients also used regionsfor application which were not guided by the nurses, 29,7% had had “difficulties” in finding a place to apply. Conclusion: the study strengthens the necessityof the direct accompaniment by a nursing professional, although the procedures can seem easy, they require good technique for dilution, aspiration andapplication to diminish the local adverse effects, as well as the orientation on the care after the application.